(3RgQ GdBOGH hKeQ GdCdHGHs - (3EHQGgje Hf Ydj Hf Jeje GdCfUGQj, CHh ESMGb GdMUQj,J (B453 (3g` s ((3eOjfI aGQS s)
(3ChdgG (B:s
(3GdMeOddg GdPi GNJU GdEfSGf HaVjdI GdHjGf gPG GdcJGH CNJQJ ajg bWYI cGajI ef GdHdGZGJ ai GdTYQ hGdaUhd hGdNjQ hGdabQ s
(3BNQgG (B:s
(3hcd eG jaVj ef GdCehQ JYdI ef jhefG GdefXhQ heJYI ef eJY GdZQhQ Je GdSaQ GdChdjJdhg ai GdSaQ GdKGfi CdaGX JfGSH gPG GdfMh dCgd GdYUQ ai UaGJ GdahGcg hGdKeGQ s
(3GfXQ ai GdLRA GdChd GdCQbGe (B449 - 451 (3COHs
(3ocJHJ dNRGfI SYjO Hf eSYhO GdTQja GdMSfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B50 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B8s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B66 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B957s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs